The Effects of Soy Protein and Cocoa With or Without Isoflavones on Glycemic Control in Type 2 Diabetes. A Double-Blind, Randomized, Placebo-Controlled Study - Judit Konya (6684362) (2019)
Objective Soy and cocoa have been suggested to be beneficial for diabetes. The aim of this study was to identify the effects of soy protein, isoflavones, and cocoa on glycemic control parameters. Research design and methods The study was a parallel, double-blind, placebo-controlled study where patients with diet or metformin controlled type 2 diabetes were randomized to, casein soy protein with or without isoflavones (SPI, SP), and with or without cocoa (SPIC, SPC) arms for an 8 week period. Glycemic control and cardiovascular risk factors were assessed prior to and after the completion of the dietary intervention. Sixty participants completed the study. Results Soy protein improved HbA1c compared to casein (p < 0.05). The addition of isoflavones improved indices of insulin resistance and LDL [delta QUICKIE (SPI: −0.12 ± 0.04 vs. SP: 0.03 ± 0.06, p = 0.03); delta LDL (−0.27 ± 0.41 vs. 0.22 ± 0.43, p = 0.02); percentage change in HOMA (31.02 ± 54.75 vs. −14.42 ± 27.07, p = 0.02); percentage change in QUICKIE (−3.89 ± 7.07 vs. 6.11 ± 10.54, p = 0.01)]. However, the addition of cocoa provided no benefit with or without isoflavones. Summary Soy protein had intrinsic activity on glycemic control compared to casein. Isoflavones improved both insulin resistance and LDL, but cocoa did not have added benefit on these indices. Clinical Trial Registration: identifier NCT01754662. Other Information Published in: Frontiers in Endocrinology License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3389/fendo.2019.00296